Applications of somatic cell nuclear transfer in goats - Yoisungnern, Ton; Paul, Ashit Kumar (Journal of Advanced Veterinary and Animal Research, 2014)
A number of animals with genetically identical appearance can be produced by somatic cell nuclear transfer (SCNT). From current advancement of SCNT and molecular techniques, production of a transgenic animal becomes easier. Although cloning efficiency in goat is low, the ability to propagate genetically identical animals, with a gene or genes of interest, would be important for increasing productivity and ultimately the economic livelihood. In this paper, the potential applications and uses of SCNT technology like production of transgenic goat for production of quality milk and meat are discussed. DOI: http://dx.doi.org/10.5455/javar.2014.a11 J. Adv. Vet. Anim. Res., 1(2): 65-69, June 2014